2020
DOI: 10.1002/slct.202002110
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Phenols from Phenylboronic Acids in Aqueous Media Catalyzed by a Cu(0)‐Nanoparticles Biohybrid

Abstract: Selective hydroxylation of different phenylboronic acids to phenols was successfully carried out by using Cu nanoparticlesenzyme hybrid catalysts in water and room temperature. Different Cu-enzyme hybrids containing Cu(II), Cu(I) and Cu(0) nanoparticles species respectively were tested on the monohydroxylation of phenylboronic acid under these mild conditions being hybrids containing Cu(0)NPs the best catalysts, with total selectivity and formation of phenol as unique product. Also, the addition of hydrogen pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…On the other hand, previous studies have shown that by the use of other copper bionanohybrids similar to those of the present work, oxidation–reduction reactions take place through radical mechanisms. In any case, further studies would be necessary to understand better the mechanism of ROS generation, the intermediate species involved (such as • OH or O 2 •– radicals), and the destabilization of the cell wall structure.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…On the other hand, previous studies have shown that by the use of other copper bionanohybrids similar to those of the present work, oxidation–reduction reactions take place through radical mechanisms. In any case, further studies would be necessary to understand better the mechanism of ROS generation, the intermediate species involved (such as • OH or O 2 •– radicals), and the destabilization of the cell wall structure.…”
Section: Introductionmentioning
confidence: 51%
“…Thus, copper NPs (CuNPs) have been the subject of studies, and their application has been explored in various fields, such as in catalysis and bioremediation or as antimicrobial agents. , Nevertheless, CuNPs have as disadvantages their low stability under atmospheric conditions, which could lead to an undesired oxidation, high cost, and low sustainability of the methods that generate them in a pure form. Therefore, several methods have been developed based on the stabilization of CuNPs through more complex structures, such as metabolites, proteins, biopolymers, or even plant extracts. …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, CuNPs have as disadvantages their low stability under atmospheric conditions, which could lead to an undesired oxidation, and the high cost and low sustainability of the methods that generate them in a pure form. Therefore, several methods have been developed based on the stabilization of CuNPs through more complex structures, as metabolites, proteins, biopolymers or even plant extracts (Din et al, 2017;Losada-Garcia et al, 2020a, 2020b, 2020c, 2021Ltaief et al, 2021;McCarthy et al, 2020;Pavithran et al, 2020).…”
Section: Introductionmentioning
confidence: 99%